Epidemiological pattern of lung cancer in a tertiary care centre-A prospective observational study - Sreekala C; K. Anitha Kumari; Jayaprakash B (International Journal of Medical Research and Review, 2017)
Background: Lung cancer is a leading cause of morbidity and mortality worldwide. An increasing incidence of lung cancer has been observed in India.Aim of the study: To evaluate epidemiological profile oflung cancer in a tertiary care centre, South Kerala.Methodology: Prospective observational study, conducted at Medical College, Thiruvananthapuram, South Kerala, in 160 consecutive patients with histopathological diagnosis of lungcancer. Data on demography, symptoms, smoking status, physical findings, diagnostic modalities, histological diagnosis, and TNM stagewere recorded using a structured questionnaire. For inferential statistics, comparison between groups of qualitative variables were analysed by chi-square test and quantitative variables were compared by student t test. P value of less than 0.05 was considered as level of significance.Results: Out of 160 consecutive lung cancer patients, 86.9% of patients were males. Male to Female ratio is 6.6: 1.50- 59 yrs was the commonest age group affected.11.3% were nonsmokers. 67.5% of smokers were having smoking index more than 500. COPD was the commonest co morbidity (58%) in the study. Adenocarcinoma (41.9%) was the commonest histological type in our study and this was the commonest histologicaltype seen in females and nonsmokers. In smokers, squamous cell carcinoma (91.3%) was more common. 66.9% of patients were at TNM stage 3 or 4 at the time of diagnosis only 5% of patients were in surgically resectable stage.Conclusion: It was found out that Adenocarcinoma was the most frequent histopathological type and majority of patients were at advanced stage at the time of diagnosis.